PENGARUH PROFITABILITAS DAN LEVERAGE TERHADAP SUSTAINABILITY REPORT PERUSAHAAN SEBELUM DAN SESUDAH PENERAPAN E-COMMERCE (Studi Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia) - Cindy Widyawati; Nur Diana; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2022)
This study aims to determine the effect of profitability and leverage on the sustainability report before and after the implementation of e-commerce and to determine the implementation of the sustainability report before and after the implementation of e-commerce. This type of research is correlational. The population of this study are banking companies listed on the Indonesia Stock Exchange. The sampling technique used purposive sampling method by producing a sample of 4 companies with multiple regression analysis methods and Paired Samples Test. The results of this study indicate that profitability has a significant positive effect on the Sustainability Report of banks listed on the BEI. Leverage has a significant positive effect on the Sustainability Report of banks listed on the IDX. There are differences in the implementation of sustainability reporting before and after the implementation of e-commerceKeywords: Profitability, Leverage and Sustainability Report